COMPARATIVE EFFICACY OF HAND HYGIENE TECHNIQUES FOR REMOVING BACTERIA FROM THE HANDS OF HEALTH CARE WORKERS WITH MICROBIOLOGICAL EVALUATION.: Life Sciences-Microbiology - SHEENAL BHATIA; DR. UJJWALA DEHANKAR (International Journal of Life Science and Pharma Research, 2022)
Hand hygiene is the simplest and most effective measure for preventing cross-transmission of micro-organisms. The impact of hand hygiene depends not only on the regularity and thoroughness of the procedures used but also on the type of hand washing agent selected. Failure to perform appropriate hand hygiene practice is a leading cause of health care associated infections. This study was conducted to compare the bacterial efficaccy of various hand hygiene techniques and to isolate the common skin contaminants from the hands of health care worker. Methodology: This prospective study was conducted in a tertiary care centre over a period of 2 months. The study included 90 volunteers i.e. 60 nurses and 30 doctors from all surgical and medical wards and ICUs. The volunteers were divided into 3 groups, one group performed handwashing with unmedicated soap, second group with medicated soap and third group performed handrubbing with alcohol based solution .Total 180 samples were collected on Trypticase soy agar by direct imprints of fingertips of the dominant hand of the HCWs before and after the hand hygiene procedure.. Potential pathogenic bacteria from transient bacterial flora were identified using standard microbiological techniques. Data was analysed with microsoft excel and by percentage analysis method. Result: Handwashing with medicated and unmedicated soap and use of alcohol based hand rub showed significant reduction in the bacterial growth on the hands of HCWs i.e. 83.4% for alcohol-based hand rub, 16.7% and 6.7% for medicated and unmedicated soap respectively. Hand contamination was found to be maximum with Coagulase-negative staphylococci (CoNS) in both before and after hand hygiene procedures. Conclusion: Alcohol based hand rub is far more efficient, convenient and time saving as compared to handwashing specially in situation in which the handwashing compliance rate is hampered.